1995
DOI: 10.3386/w5306
|View full text |Cite
|
Sign up to set email alerts
|

"Generic Entry and the Pricing of Pharmaceuticals"

Abstract: During the 1980s the share of prescriptions sold by retail pharmacies that was accounted for by generic products roughly doubled. The price response to generic entry of brand-name products has been a source of controversy. In this paper we estimate models of price responses to generic entry in the market for brand-name and generic drugs. We study a sample of 32 drugs that lost patent protection during the early to mid-1980s. Our results provide evidence that brand-name prices increase after generic entry and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
210
2
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(226 citation statements)
references
References 4 publications
11
210
2
3
Order By: Relevance
“…While most empirical studies examining incumbent responses to entry focus on tactical changes such as adjusting prices, quality levels or production capacity (e.g., Lieberman 1987;Yamawaki 2002;Frank and Salkever 2004;Simon 2005;Seamans 2009), our theoretical analysis generates several predications related to firms' strategic decisions. Reduced-form regressions are more amenable than structural estimation to testing these predications for a couple of reasons.…”
Section: Empirical Implicationsmentioning
confidence: 99%
“…While most empirical studies examining incumbent responses to entry focus on tactical changes such as adjusting prices, quality levels or production capacity (e.g., Lieberman 1987;Yamawaki 2002;Frank and Salkever 2004;Simon 2005;Seamans 2009), our theoretical analysis generates several predications related to firms' strategic decisions. Reduced-form regressions are more amenable than structural estimation to testing these predications for a couple of reasons.…”
Section: Empirical Implicationsmentioning
confidence: 99%
“…As far as we know, few econometric estimations have been applied to the pharmaceutical sector in Brazil, with both attempting to measure the impact of the entry of generics on prices. Fiuza and Lisboa (2003) indicated that the prices of brand drugs would increase with an increase in the market power of similar ones, a similar result to that of Frank and Salkever (1997), but the database used was from prior to the Generics Act. Nishijima (2008) used a different sample (covering both the period prior to and the period after the Generics Act) and a different model from that of Fiuza and Lisboa (differences-in-differences) and obtained different results, in which the price of the reference drugs would fall in accordance with a greater number of generics.…”
Section: Introductionmentioning
confidence: 50%
“…28 This prevalence of generic drugs may discourage pharmaceutical innovations and developments in the future, possibly requiring the introduction of policies that extend the length of patent periods in order to encourage brand-name companies to continue producing new and innovative drugs. [28][29][30] Despite these drawbacks, the significantly lower prices of generic drugs in the US warrant consideration of the effects of government policy on pricing, and the benefits of fostering competition within the generic drug market.…”
Section: United Statesmentioning
confidence: 99%
“…However, with the repeal of these laws and the introduction of the Waxman-Hatch Act, generic drugs were made available to the public with prices driven down by consumer market forces. 28,29 Although there were several contributing factors, the Waxman-Hatch Act is attributed to the progressive shift in the increased prescription of generic drugs, from 10 percent in the early 1980s to approximately 40 percent in the 1990s. 29 It is important to examine the Waxman-Hatch Act from numerous angles, including the effects of generic drug sales on drug innovations.…”
Section: United Statesmentioning
confidence: 99%
See 1 more Smart Citation